Determinants of decision making air traffic controllers in the air traffic control - Рева, О.М.; Дмитрієв, С.О.; Селезньов, Г.М. (Proceedings of National Aviation University (archive), 2009)
Taking into account the importance of the human factor’s influence to the flight safety while control air traffic and the special role of the data reduction processes, it is proposed corresponding model, which considers the factors of uncertainty, cognitive complexity, time deficit and stress in the process of decision making. It is determined the nature of information, which is used in the air traffic control systems. Concept is examined and are developed recommendations regarding the guarantee of an air traffic controller with working conditions in the regime of active operator, and also systematic recommendations regarding the organization of their professional preparation taking into account the facts indicated.